General characteristics of morphometric parameters nerve structures of the tentorium cerebelli - Malakhov, S. S. (Journal of Education, Health and Sport, 2018)
Objective. Establish morphometric features of the position, shape and size of tentorium cerebelli nerves in middle-aged people. Methods - macro and microscopic examination of tentorium cerebelli and its nerve structures, morphometry of all departments of tentorium cerebelli, microscopic study of the structure and innervation of tentorium cerebelli leaves stained with hematoxylin-eosin, and also by the Schubich-Hodos method using Schiff’s reagent, individual preparations impregnated by the method of Rasskazova-Kupriyanov. The obtained data were systematized from the position of the doctrine V.M. Shevkunenko about individual anatomical variability and were substantiated by means of a variational-statistical analysis. Results. The study found that the main source of innervation of tentorium cerebelli is tentorial nerve. There are two main forms of the branching of tentorial nerve in the tissue tentorium cerebelli: one-sided and double-sided. The diameter of the nerve trunks of tentorial nerve reaches values from 2.70 to 3.16 mm in men and 2.46 to 2.98 mm in women; the diameter of the lateral and medial branches does not exceed 1.55-2.30 mm (men) and 1.47-2.12 mm (women); the diameter of the intermediate twigs is 500-900 microns in the first and 350-920 microns in the others; the diameter of the fins is 40-170 and 10-160 microns. The highest rates of brachicephals are slightly reduced in mesocephals, and reach the smallest values in the dolichocephals. The length of the trunks tentorial nerve is in the range from 1.50 to 2.28 cm; the length of the main branches does not exceed 2,05-3,10 cm; the length of the zone of innervation of the terminal branches of the tentorial nerve is from 1.40 to 1.95 cm. This parameter has the highest rates in people with a dolichocephalic form of the head, the smallest - in people with brachycephalic form.